(3JGQjN GdQSd hGdedhcs - (3eMeO Hf LQjQ Hf jRjO GdWHQj , GHf LQjQ, CHh LYaQ, J (B310 (3g` s
(3ChdgG (B:s
(3jHJOF HCMOGK SfI (B133(3g` , Hbhdg (B: (3PcQ eG cGf aigPg GdSfI ef GdCMOGK aef Pdc eG cGf ef JhLjg CHj GdYHGS Yeg SdjeGf Hf Ydi hGdjkG Ydi GdHUQI hCYeGdgG hchQOLdI hGdHMQjf hYeGf s
(3BNQgG (B:s
(3jfJgi HCKfGA CMGOK SfI (B145(3g` , Hbhdg (B: (3hai gPg GdSfI YfgG HYO ebJd eMeO Hf YHO Gddg hai gPg GdSfI KGQJ GdShOGf HGdeOjfI Ydi YHO Gddg Hf GdQHjY agQH efge s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde fSN LjO eVHhWs
(3heged GdfbW CMjGfkGs
(3HChdgG hba HJGQjN (B767(3g` s
(3hJedc ZjQ eDQN deMeO Hf CMeO NWjH OGQjG ef VhGMi OeTb s
(3fSNI KGfjI s
Keywords: (3GdJGQjNs